2008
DOI: 10.1115/1.2910825
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Painlevé Paradox in a Robotic System

Abstract: This paper aims at experimentally investigating the dynamical behaviors when a system of rigid bodies undergoes so-called paradoxical situations. An experimental setup corresponding to the analytical model presented in our prior work [28] is developed, in which a two-link robotic system comes into contact with a moving rail. The experimental results clearly show that a tangential impact does exist at the contact point and takes a peculiar property well coinciding with the maximum dissipation principle stated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 32 publications
2
42
0
1
Order By: Relevance
“…The process of impact is dominated by the contact point with maximal potential energy, which is linked with the 'time-like' independent variable Zhao et al 2008). Similar to the contact dynamics, the tangential constraint at the instant of the relative tangential velocity vanishing can also be identified by the correlative coefficient ðm st i Þ obtained from the local dynamical equations.…”
Section: Introductionmentioning
confidence: 99%
“…The process of impact is dominated by the contact point with maximal potential energy, which is linked with the 'time-like' independent variable Zhao et al 2008). Similar to the contact dynamics, the tangential constraint at the instant of the relative tangential velocity vanishing can also be identified by the correlative coefficient ðm st i Þ obtained from the local dynamical equations.…”
Section: Introductionmentioning
confidence: 99%
“…The impact assumption has been supported by the numerical investigations fulfilled under a variety of compliance-based models [12,13]. In addition, experimental investigations [28] also showed that the unstable phenomenon of a robotic system touching a moving belt essentially originated from an event of a tangential impact.…”
Section: Introductionmentioning
confidence: 77%
“…If and only if A(θ, μ) > 0, the solution obtained from the constraint-based method is unique for all B(θ,θ) [18,28]. If A(θ, μ) < 0, the normal contact force F n is either in an inconsistent mode if B(θ,θ) < 0, or is in an indeterminate mode if B(θ,θ) > 0.…”
Section: Painlevé Paradoxmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining a Lagrangian function L = T − U and using Euler-Lagrange equations, the dynamics of the system is governed by 14) where…”
Section: The Dynamics Of a Disc-ball Systemmentioning
confidence: 99%